2020
DOI: 10.1515/jpm-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune responses in amniotic fluid of women with a sonographic short cervix

Abstract: Objectives A sonographic short cervix is one of the strongest predictors of preterm delivery. However, the cellular immune composition of amniotic fluid in women with a short cervix has not yet been described. Herein, we determined cellular and soluble immune responses in amniotic fluid from pregnant women with a mid-trimester asymptomatic short cervix. Methods Amniotic fluid samples (n=77) were collected from asymptomatic wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 116 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…(28)(29)(30)(31)(32)(33)] and cellular [e.g. innate and adaptive immune cells (34)(35)(36)(37)(38)(39)(40)] components that serve as an immunological barrier against invading pathogens. In clinical medicine, amniotic fluid is utilized as a diagnostic tool for assessing intra-amniotic inflammation and/or infection (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), a condition that is strongly associated with obstetrical disease, the most detrimental of which is preterm birth (60).…”
Section: Introductionmentioning
confidence: 99%
“…(28)(29)(30)(31)(32)(33)] and cellular [e.g. innate and adaptive immune cells (34)(35)(36)(37)(38)(39)(40)] components that serve as an immunological barrier against invading pathogens. In clinical medicine, amniotic fluid is utilized as a diagnostic tool for assessing intra-amniotic inflammation and/or infection (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), a condition that is strongly associated with obstetrical disease, the most detrimental of which is preterm birth (60).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of SPTB in asymptomatic women with a sonographic short cervix increases as cervical length decreases 14 . Previous reports have demonstrated that a shorter cervix is associated with a more severe inflammatory response in the amniotic cavity 15 . Further analysis are necessary to analyze proteins concentration in the second‐trimester amniotic fluid of women according to cervical length.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Previous reports have demonstrated that a shorter cervix is associated with a more severe inflammatory response in the amniotic cavity. 15 Further analysis are necessary to analyze proteins concentration in the second‐trimester amniotic fluid of women according to cervical length. In addition, amniotic fluid protein levels may significantly fluctuate during the antenatal period, and it is not certain that the presented differences persist (or even increase) in the third trimester and contribute to preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils represent a primary cellular component of innate immunity that protects against microorganisms invading the amniotic cavity through an array of host defense mechanisms 167 , which may include phagocytosis 168 , the release of antimicrobial products and cytokines 75 , 169 178 , and the formation of neutrophil extracellular traps 178 – 180 . Yet, neutrophils also form a physiological component of the AF cellular repertoire throughout pregnancy 181 ; therefore, they are present in women diagnosed with a short cervix 182 . Herein, we found that biological processes, such as neutrophil-mediated immunity, neutrophil activation, granulocyte activation, myeloid leukocyte activation, and myeloid leukocyte-mediated immunity, were impacted by protein differential abundance in women who delivered within two weeks of the diagnosis of a short cervix.…”
Section: Discussionmentioning
confidence: 99%